The influence of the local government on reducing youth unemployment and youth perception on the work of local authorities in the area of employment in the Jegunovce and Cair Municipality - Rustemi, Agron; Memeti, Memet (Ревија за социјална политика/Journal of Social Policy, 2014)
Unemployment is one of the most prevalent issues that the Republic of Macedonia has faced sin ce its independence. In addition to the cen tral government which is responsibility for the design and implementation of policies in the area of employment, the local government another important actor, who can contribute in this area, through the local economic development policies. This article will analyze va ri ous theoretical approaches of the concept of unemployment, factors that are associated with unemployment and the impact of unemployment on the overall well-being of citizens as well as the perception of citizens on unemployment in the municipalities of Jegunovce and Cair.
Keywords: local government; youth; Chair; Jegunovce; unemployment